In some parasitic diseases of the lungs in Peru - Corvetto, Aníbal (1922)
Among parasitic diseases of the lungs is, without dispute, the most widespread everywhere and in Peru, of course, infection with the tubercle bacillus; pulmonary tuberculosis. However it is not the condition that I want to deal for doing so and before others and myself; and because it is a thing well known how to proceed to clinical diagnosis with accuracy and timeliness, to institute appropriate prophylactic treatment and take measures if required.